Graphic Design Solutions - Landa, Robin (Australia Wadsworth/Cengage Learning, 2011)
A comprehensive, how-to reference on graphic design and advertising for print and interactive media. It stresses theory and applications with an instructive approach. It focuses on the integration of design principles and elements, providing hundreds of meaningful examples of their interaction throughout.
Include Index, Glossary and Illustration
Keywords: Graphic arts -- Commercial art